Salinity stress tolerance in Vigna species: insights into adaptive responses and innovative approaches for sustainable agriculture - Suriya, Sekar; Selvaraj, Chinnadurai Immanuel (Frontiers in Plant Science, 2026)
Legumes are widely recognised as important protein sources; among them, Vigna species are recognised for their substantial protein content, approximately 20–25%, and play an important role in global nutrition. However, yield is severely reduced when groundwater with elevated salinity levels is used for irrigation. Salinity is a significant abiotic stress that substantially decreases agricultural yield, particularly in irrigated and less fertile areas. In Vigna species, salt stress causes impaired seed germination, delayed seedling growth, nutrient uptake deficits, inhibition of photosynthetic mechanisms, disruption of plant hormone homeostasis and oxidative stress. The primary cause of these effects is due to the excessive accumulation of Na+ and Cl-, which leads to ion toxicity and significant yield loss. To minimise these effects, Vigna species have certain adaptation strategies such as antioxidant enzyme activity, osmoprotectant accumulation, vacuolar compartmentalisation, ion exclusion, hormonal adjustment, and maintenance of ion homeostasis. Besides inherent tolerance mechanisms, recent approaches such as the exogenous application of nutrients, biostimulants, seed priming, plant growth-promoting rhizobacteria and nanotechnology can improve plant nutrient uptake and stress resilience under salinity. Furthermore, biotechnology interventions such as marker-assisted breeding, transgenic approaches, gene editing, and omics-based strategies have promising potential for developing salt-tolerant Vigna genotypes. This review specifically examines the physiological, biochemical, and molecular responses of Vigna species to salinity and evaluates various mitigation strategies. By highlighting recent advances and identifying key research gaps, this review provides insights for developing integrated and sustainable approaches to enhance salinity tolerance in Vigna species, thereby supporting sustainable agriculture and global food security.